ANALYSIS OF MONZA TRADERS' SURVIVAL STRATEGIES IN FACING THE DIGITAL MARKET - Rizqiya, Annisa; Berutu, Irsyadiah Dermaini; Maulana, Rifki; Aisyah , Siti (PERSPEKTIF: Journal of Social and Library Science, 2024)
This study aims to examine the survival strategies of Monza traders in Pajak Melati, Medan, in facing the challenges of digitalization that change traditional trading patterns to technology-based ones. Digitalization provides opportunities to expand the market, but also presents challenges in the form of tight competition with e-commerce platforms and low adoption of technology by traditional traders. This study uses a descriptive qualitative method with data collection through in-depth interviews, participant observation, and documentation studies. The research subjects consisted of five Monza traders who were selected purposively to ensure data diversity. The data obtained were analyzed using a thematic approach to identify survival strategies as well as obstacles and opportunities in adopting digital technology. The results of the study show that Monza traders implement survival strategies such as improving personal customer service, product diversification, implementing a hybrid system that combines physical and digital transactions, and competitive pricing strategies. The main obstacles found were low digital literacy of traders, limited capital to invest in technology, and tight competition with digital platforms that offer lower prices and wider market reach. On the other hand, there are great opportunities such as access to a wider market through digital media, operational efficiency with technology, changes in consumer shopping patterns that are more online, and support from government programs in the form of training and subsidies. This study concludes that Monza traders in Pajak Melati are able to adopt various creative strategies to survive in the digital era, although they still face obstacles that require systematic solutions such as increasing digital literacy and access to capital. This study contributes to providing insight into the adaptation of traditional traders to digitalization, especially in the traditional market sector with specific local characteristics.